The Impact of Institutional Performance and Environmental Sustainability on Foreign Direct Investment in Pakistan - Arslan, Syed Muhammad; Kanwal, Amna; Kazmi, Syed Muhammad Farman Ali; Rahman, Saif Ur (iRASD Journal of Economics, 2023)
In the context of Pakistan, this study aims to investigate how environmental sustainability, institutional performance, financial inclusion, and economic growth interact with and affect foreign direct investment .to determine if there are substantial causal linkages or correlations between these factors, as well as how these independent variables affect FDI inflows and outflows in Pakistan. The study also intends to offer insights on how individuals and governments may support FDI in the Pakistani setting. The research uses time-series data collected from 1997 to 2022 from the (ICRG) and (WDI) .It uses NARDL modelling to analyses the dynamic relationships between FDI, environmental sustainability, institutional performance, financial inclusion, and economic growth in the context of Pakistan. Unit root tests are used to evaluate each factor's stationarity. It seeks to clarify the short- and long-term correlations between these factors by doing this. The NARDL approach reveals substantial discrepancies in the connection among independent variables and foreign direct investment. The study finds connections between FDI and the selected independent variables that are both short- and long-term with positive and negative shocks. Foreign direct investment (FDI) benefits from institutional performance and economic development in both the short and long run, although it is less immediately influenced by financial inclusion and environmental sustainability. This highlights not just the need for more research to explore the collateral advantages of sustainability and financial inclusion, but also the necessity of supporting institutions and economic growth to attract foreign direct investment. To attract more foreign direct investment, Pakistan may really promote measures that support economic growth and institutional effectiveness. This adds to the body of scholarly research and offers useful advice to stakeholders and policymakers who want to maximize FDI inflows while fostering inclusive and sustainable economic growth in Pakistan.